Bakery Industry Training Assistance For Excellent Service Agency (ESA) Training Center Malang - Yulistiani, Ratna; Sihananto, Andreas; Kartini, Kartini; Trimono, Trimono (International Journal Of Community Service, 2023)
Excellent Service Agency (ESA) is an educational institution for the service and service industry in the city of Malang, which is engaged in training in the hospitality industry, especially in the fields of tourism, hospitality, and selfdevelopment. ESA has difficulties in providing professional HR education in the bakery industry due to a lack of equipment, besides that ESA also lacks insight into food safety to support the quality of bakery products that will be produced, even though safety assurance is one of the determinants of competitiveness in both the domestic and international markets. ESA is also less able to expand its market share because it has not implemented digital marketing. The methods that have been carried out include: 1)Assisting ESA with 5 types of bakery processing equipment for ESA to train more professional human resources in the F&B field; 2). Training on Good Manufacturing Practice (GMP) and Food Sanitation; 3) Training and practice of diversifying bakery and cake processing from wheat flour and composite flour; The results of this activity include increasing understanding and insight for ESA employees and students as well as UPN Veterans East Java students about 1. The Role of Good Manufacturing Practice (GMP) and Food Safety for the Bakery Industry; and 2. Basic Theory and Diversification of Bakery Product from Wheat Flour and Composite Flour.